2016
DOI: 10.1007/s11207-016-1023-x
|View full text |Cite|
|
Sign up to set email alerts
|

A Recount of Sunspot Groups on Staudach’s Drawings

Abstract: We have examined the more than 1100 drawings of the solar disk made by the German astronomy amateur Johann Caspar Staudach during 1749-1799 and counted the spots on each image. Using the modern perception of how to group spots into active regions we regrouped the spots as a modern observer would. The resulting number of groups was found to be on average 25% higher than the first count of groups performed by Wolf in 1857, and used by Hoyt and Schatten in their construction of the Group Sunspot Number. Compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 5 publications
1
22
0
Order By: Relevance
“…Accumulating the light, telescopes could help a little to make out dark-dark bluish plasma tail in the night sky. However, early telescopes likely suffered from spherical and chromatic aberration (Svalgaard, 2017). Therefore, the first hint of plasma tail we figured out only for Great comet C/1769 P1.…”
Section: Discussionmentioning
confidence: 94%
“…Accumulating the light, telescopes could help a little to make out dark-dark bluish plasma tail in the night sky. However, early telescopes likely suffered from spherical and chromatic aberration (Svalgaard, 2017). Therefore, the first hint of plasma tail we figured out only for Great comet C/1769 P1.…”
Section: Discussionmentioning
confidence: 94%
“…While in earlier parts of the series physical closeness of spots was considered a sufficient criterion, since the mid-twentieth century evolutionary information is also taken into account, sometimes resulting in the division into several groups of what would have been considered as a single group by early observers. Svalgaard et al (2017) estimate that this effect may have inflated Waldmeier's sunspot numbers by 4-5% relative to earlier counts, while the effect on the late eighteenth century sunspot reconstruction of the SSN by Wolf based on the drawings of Staudacher may be even larger, reaching 25% (Svalgaard 2017). On the other hand, Izenman (1983) notes that Waldmeier's authoritative 1965 edition of the R Z series does contain slight corrections also to the data published previously, in 1925 by Wolfer.…”
Section: Revisionmentioning
confidence: 96%
“…Svalgaard (2016) has shown that modern group-splitting will increase Staudacher's counts (made by Wolf in the 19th century from Staudacher's drawings and subsequently used by Hoyt and Schatten) by an additional 25% (or 30%; Usoskin et al 2016a), yielding a net scaling (k 0 ) (or correction) factor of~2 relative to a modern reference observer.…”
Section: Long-term Behavior Of the K 0 Seriesmentioning
confidence: 99%